Modern aspects of atibiotic sensitivity of prominent pathogens of infectious complications - Nazarchuk O.A.; Osadchuk N.I.; Palij D.V. (Medičnì Perspektivi)
In the research antibiotic sensitivity of opportunistic pathogens was studied. In 2011-2015 from 405 patients with burns there were isolated clinical strains of S. aureus (n 130), P. aeruginosa (n 127), A. baumannii (n 176), being the prominent pathogens of infectious complications. Clinical strains of S. aureus, P. aeruginosa, A. baumannii obtained all morphological, tentorial, cultural and biochemical qualities, typical for these species of bacteria. On the basis of the received results there was carried out approximation and interpolation of these data, dynamic prognostic indexes of changes in S. aureus, P. aeruginosa, A. baumannii antibiotic sensitivity were obtained. Low sensitivity to ampicillini/sulbactam (58,63±8,58%), ceftriaxone (55,75±14,24%), gentamicin (57,92±10,76%), tobramycin (64,67±10,3%) in clinical strains of S. аureus was proved. Prognostic optimizations of S. аureus sensitivity to amoxicillini/clavulanat (82,35%), gatifloxacin (94,12%) were determined. Clinical strains of P. aeruginosa, A. baumannii were shown to have low sensitivity to ceftazidime, cefoperazone, cefoperazone/sulbactam (20,08±2,98%; 48,88±6,49%, respectively). Progressive decrease of sensitivity to amikacin in P. aeruginosa (29,77±7,55%), A. baumannii (17,0±1,34 %) and to gatifloxacin in P. aeruginosa (28,53±1,35%), isolated from patients with burns were determined.